Positive and negative plates of tubular lead-carbon battery and preparation method of positive and negative plates

By adopting tube structure and specific ratio active substance powder in the positive and negative electrode plates of lead-carbon batteries, the problem of poor stability of lead paste is solved, significantly extending the battery life and improving circulation performance and charging capacity.

CN119275245APending Publication Date: 2025-01-07张率率
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411437344.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

During the circulation process, the positive and negative electrode plates of existing lead-carbon batteries have poor stability and are prone to fall off due to the uneven dispersion of barium sulfate and carbon materials, which reduces the life of the battery.

Method used

The lead-carbon battery positive and negative electrode plate adopts a tube-type structure, by filling the conductive core and sleeve with active substance powder, including lead powder, capacitive carbon material, barium sulfate, sodium lignin sulfonate, humic acid and staple fibers, Form a stable lead paste structure to ensure the stability and uniformity of lead paste.

Benefits of technology

It significantly improves the cycling performance of the battery, extends the battery life, and provides better charging reception and low-temperature startup performance in the fields of hybrid vehicles and new energy storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275245A_ABST
    Figure CN119275245A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lead-acid storage batteries, in particular to tubular lead-carbon battery positive and negative plates and a preparation method thereof. The positive and negative pole plates of the tubular lead-carbon battery comprise positive and negative pole plate grids and filled active substance powder, the positive and negative pole plate grids are of a fence structure formed by cross beams and conductive cores perpendicular to the cross beams, and a sleeve layer is arranged outside the positive and negative pole plate grids; the active substance powder is filled in a gap between the sleeve layer and the conductive core; the active substance is prepared from the following substances in percentage by weight: 1 to 25 weight percent of lead powder, 1 to 50 weight percent of capacitive carbon material, 0.1 to 0.5 weight percent of carbon black, 2 to 97 weight percent of barium sulfate, 0 to 1.2 weight percent of sodium lignin sulfonate, 0.5 to 2 weight percent of humic acid and 0.05 to 0.1 weight percent of short fiber. The manufacturing process is simple and easy to implement, solves the problems that the lead paste is poor in stability and easy to fall off, stabilizes the structure of the lead paste, prevents the lead paste from falling off, and prolongs the service life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lead-acid batteries, in particular to positive and negative plates of a tubular lead-carbon battery and a preparation method thereof. Background Art

[0002] As the oil shortage and urban environmental problems become increasingly prominent, vigorously developing the new energy industry and the electric vehicle industry have become two important issues facing the sustainable development of the national economy. As a device for energy storage and conversion, secondary power supplies have become the key to restricting the development of these two industries.

[0003] Lead-acid batteries have gone through nearly 150 years of development. They have the advantages of abundant raw material sources, good safety and reliability, high cost performance, and recyclability. They occupy an important position in the field of secondary power sources. They have made great progress in theoretical research, product types and varieties, and product electrical performance. Whether in transportation, communications, electricity, military, or in various economic fields such as navigation and aviation, lead-acid batteries have played an indispensable and important role. With the continuous development of new energy storage and power markets, higher requirements are also put forward for the energy density, power density and cycle life of lead-acid batteries. Especially in hybrid vehicles and intermittent new energy storage applications, secondary batteries are required to have good charge acceptance and long cycle life in partial charge state. Under such working conditions, the positive plate of traditional lead-acid batteries is prone to mud and powdering, and coarse "inert" lead sulfate crystals are easily formed on the surface of the negative electrode. In the subsequent charging process, they cannot be reversibly converted into lead, which leads to a decrease in the battery's charge acceptance and deteriorates the battery cycle performance.

[0004] Lead-carbon battery is a capacitor-type lead-acid battery. Carbon materials with high specific surface area and high capacitance activity and barium sulfate materials are added to the positive and negative electrodes of the lead-acid battery. They can absorb instantaneous large currents and inhibit surface sulfation, so that the battery has both high capacity and high power characteristics. The positive electrode active material of ordinary lead-acid batteries is lead oxide (PbO2), and the negative electrode active material is lead (Pb). If the positive and negative electrode active materials Pb are all replaced with barium sulfate and carbon materials, the ordinary lead-acid battery becomes a hybrid capacitor; if barium sulfate and carbon materials are mixed into the positive and negative electrode active materials Pb, the ordinary lead-acid battery becomes a lead-carbon battery. It combines carbon materials (C) with barium sulfate and double-layer capacitance characteristics with sponge-like (Pb) negative electrodes to make Lead-carbon bifunctional composite electrodes (hereinafter referred to as Lead-carbon electrodes) with both capacitance characteristics and battery characteristics. The Lead-carbon composite electrode is then matched with the PbO2 positive electrode to assemble into a Lead-carbon battery. Lead-carbon battery is a new type of super battery. It combines lead-acid battery and supercapacitor into one: it has the advantages of instant large-capacity charging of supercapacitor and the energy density advantage of lead-acid battery. It also has very good charging and discharging performance and can be fully charged in 90 minutes (if lead-acid battery is charged and discharged in this way, its life span is less than 30 times).

[0005] At present, the positive and negative plates of the existing lead-carbon battery are generally a structure in which lead paste is coated on a substrate. In the active material mainly composed of lead powder, activated carbon accounting for 0.1-10wt.% of the total weight of the lead paste is added. The active material is added with water and 1.0-1.4g / cm 3 The lead paste is coated on a lead-calcium alloy substrate and dried to prepare a carbon additive having a specific surface area of ​​1000-3000m 2 / g. Due to the large difference in density between carbon and lead, directly mixing barium sulfate and carbon materials into the positive and negative lead pastes will cause problems such as difficulty in evenly dispersing barium sulfate and carbon materials and poor bonding between the lead paste and the plate. The uneven mixing of barium sulfate, carbon materials and lead powder will affect the stability of the positive and negative electrode pastes and reduce the strength of the plate. Directly adding a large amount of barium sulfate and carbon into the positive and negative lead pastes will easily cause the lead paste to fall off during the cycle, reducing the life of the battery. Summary of the invention

[0006] The purpose of the present invention is to provide a positive and negative electrode plate of a tubular lead-carbon battery and a preparation method thereof, so as to solve the problems of poor stability and easy falling off of lead paste, stabilize the lead paste structure, prevent the lead paste from falling off, and extend the service life of the battery.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is: A tubular lead-carbon battery positive and negative plates, including positive and negative grids and filled active material powder, wherein the positive and negative grids are fence structures composed of a crossbeam and a conductive core perpendicular thereto, and are characterized in that: a sleeve layer is arranged outside the positive and negative grids; the active material powder is filled in the gap between the sleeve layer and the conductive core; the active material is composed of the following substances in weight percentage: 1~25wt% lead powder, 1~50wt% capacitive carbon material, 0.1~0.5wt% carbon black, 2~97wt% barium sulfate, 0~1.2wt% sodium lignin sulfonate, 0.5~2wt% humic acid and 0.05~0.1wt% short fiber.

[0008] Furthermore, the material of the positive and negative electrode grids is one of metal, carbon foam or hard plastic; the metal is one of lead, copper, titanium, tantalum, tungsten and aluminum.

[0009] Furthermore, when the material of the positive and negative electrode grids is not lead, their surfaces are lead-plated.

[0010] Furthermore, the material of the sleeve layer is polyester or non-woven fabric; the cross-section of the sleeve layer is circular, oval or rectangular.

[0011] Furthermore, the active material powder is composed of the following substances in weight percentage: 2~20wt% lead powder, 2~20wt% capacitive carbon material, 0.1~0.5wt% carbon black, 3~80wt% barium sulfate, 0.2~0.9wt% sodium lignin sulfonate, 0.5~2wt% humic acid and 0.05~0.1wt% short fibers.

[0012] Furthermore, the carbon black has a specific surface area of ​​less than 50 m 2 / g.

[0013] Furthermore, the short fibers are polyethylene terephthalate or polybutylene terephthalate.

[0014] The method for preparing the positive and negative plates of the tubular lead-carbon battery of the present invention comprises the following steps: 1. Assembly: Put the sleeve on the positive and negative grids; 2. Mixing materials: Evenly mix lead powder, capacitive carbon material, carbon black, barium sulfate, sodium lignin sulfonate, humic acid and short fibers; 3. Powder filling: Pour the raw materials obtained in step 2 into the casing layer, fully fill the gaps in the casing layer, and buckle the bottom seal; 4. Acid immersion and drying: Immerse the tubular plate obtained in step 3 in sulfuric acid for 15 minutes to 2 hours, take it out and dry it at 65°C.

[0015] Furthermore, the method for preparing the positive and negative plates of the tubular lead-carbon battery comprises the following steps: 1. Assembly: Put the sleeve on the positive and negative grids; 2. Mixing: Evenly mix lead powder, carbon black, barium sulfate, sodium lignin sulfonate, humic acid and short fibers; 3. Powder filling: Pour the raw material obtained in step 2 into a part of the casing layer, and pour the capacitive carbon material into the remaining casing layer, fully fill the gaps in the casing layer, and buckle the bottom seal; 4. Acid immersion and drying: Immerse the tubular plate obtained in step 3 in sulfuric acid for 15 minutes to 2 hours, take it out and dry it at 65°C.

[0016] Furthermore, in step 4, the density of the sulfuric acid is 1.0-1.3 g / cm 3 The drying time is 24 to 36 hours.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The manufacturing process is simple and easy to implement; 2. Compared with lead-carbon flat plate electrodes, it can achieve the addition of high content of barium sulfate and carbon materials without causing lead paste to fall off or reducing the strength of the plate. It can give full play to the capacity characteristics of lead and carbon, buffer instantaneous large current, inhibit the mudding of the positive plate surface and the sulfation of the negative electrode surface, and significantly improve the HRPSoC cycle performance of the battery; 3. Stabilize the lead paste structure, prevent the lead paste from falling off, and extend the service life of the battery. It has broad application prospects in the fields of hybrid vehicles and solar energy and wind energy storage; 4. The addition of barium sulfate and carbon materials, when the battery is working under frequent instantaneous high current charge and discharge, the barium sulfate material and carbon material with capacitance characteristics mainly release or receive current, inhibiting the "positive electrode mud and negative electrode sulfation" of the lead-acid battery, effectively extending the battery life; when the battery is in a long-term low current operation, it is mainly the positive plate and the sponge lead negative electrode that work to continuously provide energy; 5. The high barium sulfate and carbon content make the electrode have better low-temperature starting ability, charge acceptance and large current charge and discharge performance than traditional lead-acid batteries; at the same time, the addition of barium sulfate and activated carbon improves the power density of the battery and extends the cycle life. At the same time, because barium sulfate and activated carbon occupy part of the electrode space, the energy density is reduced and the amount of electrode gas evolution may also increase. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 A schematic diagram of the structure of an embodiment of the present invention (1); Figure 2 This is a structural schematic diagram (2) of an embodiment of the present invention.

[0019] In the figure: 1. Positive and negative electrode grids; 2. Row pipes; 3. Active material powder. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. Example

[0021] like Figure 1 , 2 As shown, the positive and negative plates of the tubular lead-carbon battery described in this embodiment include positive and negative grids 1 made of lead-calcium multi-element alloy with lead plating treatment on the surface and filled with active material powder 3. The positive and negative grids 1 are fence structures composed of a crossbeam and a conductive core perpendicular to it. A sleeve layer of non-woven fabric material is arranged outside the positive and negative grids 1. The gap between the sleeve layer and the conductive core is filled with active material powder 3, and the active material powder is composed of the following substances in weight percentage: 1wt% lead powder, 20wt% capacitive carbon material, 0.4wt% carbon black, 75wt% barium sulfate, 0.1wt% sodium lignin sulfonate, 0.5wt% humic acid and 0.09wt% short fiber.

[0022] The cross section of the sleeve layer is circular.

[0023] The capacitive carbon material comprises 5 wt% of activated carbon, 2 wt% of expanded graphite, 2 wt% of carbon fiber and 1 wt% of graphene.

[0024] The carbon black specific surface area is less than 50m 2 / g; the short fiber is polyethylene terephthalate.

[0025] The method for preparing the positive and negative plates of the tubular lead-carbon battery described in this embodiment comprises the following steps: 1. Assembly: Put the sleeve on the positive and negative grids; 2. Mixing materials: Evenly mix lead powder, activated carbon, expanded graphite, carbon fiber, graphite, carbon black, barium sulfate, sodium lignin sulfonate, humic acid and short fibers; 3. Powder filling: Pour the raw material obtained in step 2 into a part of the casing layer, and pour the capacitive carbon material into the remaining casing layer to fully fill the gaps in the casing layer, and then buckle the bottom seal; 4. Acid soaking and drying: Immerse the tubular plate obtained in step 3 in a solution with a density of 1.0-1.3 g / cm 3 Sulfuric acid for 15 min, then dried at 65 °C for 24 h. Example

[0026] like Figure 1 , 2As shown, the positive and negative plates of the tubular lead-carbon battery described in this embodiment include positive and negative grids made of carbon foam material with lead plating treatment on the surface and filled with active material powder. The positive and negative grids are fence structures composed of a crossbeam and a conductive core perpendicular to it. A sleeve layer of polyester material is arranged outside the positive and negative grids, and the gap between the sleeve layer and the conductive core is filled with active material powder. The active material powder is composed of the following substances in weight percentage: 2wt% lead powder, 60wt% capacitive carbon material, 0.5wt% carbon black, 40wt% barium sulfate, 1.2wt% sodium lignin sulfonate, 2.0wt% humic acid and 0.05wt% short fiber.

[0027] The cross section of the sleeve layer is elliptical.

[0028] The capacitive carbon material comprises 10 wt% of activated carbon, 3 wt% of expanded graphite, 1 wt% of carbon black, 3 wt% of carbon fiber, 5 wt% of carbon nanotubes and 3 wt% of graphene.

[0029] The specific surface area of ​​the carbon black is less than 50m2 / g; and the short fibers are polybutylene terephthalate.

[0030] The method for preparing the positive and negative plates of the tubular lead-carbon battery described in this embodiment comprises the following steps: 1. Assembly: Put the sleeve on the positive and negative grids; 2. Mixing: Evenly mix lead powder, carbon black, barium sulfate, sodium lignin sulfonate, humic acid and short fibers; 3. Powder filling: The raw materials obtained in step 2 are poured into the sleeve layer by air pressure or vibration, and the activated carbon, expanded graphite, carbon fiber, carbon nanotubes, graphite, and carbon black in the activated carbon components are mixed and poured evenly into the remaining sleeve layer, and the bottom is buckled; 4. Acid soaking and drying: Immerse the tubular plate obtained in step 3 in a solution with a density of 1.0-1.3 g / cm 3 Sulfuric acid for 30 min, then dried at 65 °C for 36 h.

[0031] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A tubular lead-carbon battery positive and negative plates, comprising positive and negative grids and filled active material powder, wherein the positive and negative grids are fence structures composed of a beam and a conductive core perpendicular thereto, characterized in that: A set of layers is arranged outside the positive and negative electrode grids; the active material powder is filled in the gap between the set of layers and the conductive core; the active material is composed of the following substances in weight percentage: lead powder 1~25wt%, capacitive carbon material 1~50wt%, carbon black 0.1~0.5wt%, barium sulfate 2~97wt%, sodium lignin sulfonate 0~1.2wt%, humic acid 0.5~2wt% and short fiber 0.05~0.1wt%.

2. The positive and negative plates of a tubular lead-carbon battery according to claim 1, characterized in that: The material of the positive and negative electrode grids is one of metal, carbon foam or hard plastic; the metal is one of lead, copper, titanium, tantalum, tungsten and aluminum.

3. A tubular lead-carbon battery positive and negative plates according to claim 1 or 2, characterized in that: When the material of the positive and negative electrode grids is not lead, their surfaces are lead-plated.

4. The positive and negative plates of a tubular lead-carbon battery according to claim 1, characterized in that: The material of the sleeve layer is polyester or non-woven fabric; the cross section of the sleeve layer is circular, oval or rectangular.

5. The positive and negative plates of a tubular lead-carbon battery according to claim 1, characterized in that: The active material powder contains the following materials in weight percentage: 2-20wt% lead powder, 2-20wt% capacitive carbon material, 0.1-0.5wt% carbon black, 3-80wt% barium sulfate, 0.2-0.9wt% sodium lignin sulfonate, 0.5-2wt% humic acid and 0.05-0.1wt% short fiber.

6. A tubular lead-carbon battery positive and negative plates according to claim 1 or 5, characterized in that: The carbon black specific surface area is less than 50m 2 / g.

7. A tubular lead-carbon battery positive and negative plates according to claim 1 or 7, characterized in that: The short fibers are polyethylene terephthalate or polybutylene terephthalate.

8. The method for preparing positive and negative plates of a tubular lead-carbon battery as claimed in claim 1, characterized in that: The steps include: (1) Assembly: Put the jacket layer on the positive and negative electrode grids; (2) Mixing: uniformly mix lead powder, capacitive carbon material, carbon black, barium sulfate, sodium lignin sulfonate, humic acid and short fibers; (3) Powder filling: the raw materials obtained in step (2) are poured into the casing layer to fully fill the gaps in the casing layer, and then the bottom is sealed; (4) Acid immersion and drying: Immerse the tubular electrode obtained in step (3) in sulfuric acid for 15 minutes to 2 hours, take it out and dry it at 65°C.

9. The method for preparing positive and negative plates of a tubular lead-carbon battery according to claim 8, characterized in that: The steps include: (1) Assembly: Put the jacket layer on the positive and negative electrode grids; (2) Mixing: Evenly mix lead powder, carbon black, barium sulfate, sodium lignin sulfonate, humic acid and short fibers; (3) Powder filling: the raw material obtained in step (2) is poured into a part of the casing layer, and the capacitive carbon material is poured into the remaining casing layer to fully fill the gaps in the casing layer, and then the bottom is buckled; (4) Acid immersion and drying: Immerse the tubular electrode obtained in step (3) in sulfuric acid for 15 minutes to 2 hours, take it out and dry it at 65°C.

10. A method for producing positive and negative plates of a tubular lead-carbon battery as claimed in claim 8 or 9, characterized in that: In step (4), the density of the sulfuric acid is 1.0-1.3 g / cm 3 The drying time is 24 to 36 hours.